Connecting hapū māmā (pregnant women) early to a lead maternity carer: striving for equity using the Best Start-Pregnancy Tool - Rawiri McKree Jansen; Chloe Topping; Marie Jardine (Journal of Primary Health Care, 2022)
Introduction In Aotearoa New Zealand, lead maternity carers (LMCs) provide maternity care through pregnancy and birth, until 6 weeks’ postpartum. An early LMC connection in pregnancy is associated with better maternal and perinatal health outcomes. However, hapū māmā (pregnant women) may experience barriers to engaging with LMC, delaying screening, risk assessments, and education. These barriers contribute to inequitable health outcomes for Māori māmā and pēpi (Māori mothers and babies). A pro-equity approach to maternity care is warranted.